Software piracy, inequality and the poor: evidence from Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose Poverty and inequality undoubtedly remain substantial challenges to economic and human developments amid growing emphasis on IPRs (with recent advances in ICTs) and good governance. In the first empirical study on the incidence of piracy on inequality in Africa, we examine how a plethora of factors (IPRs laws, education & ICTs and government quality) are instrumental in the piracy-inequality nexus. Design/methodology/approach Two-Stage-Least Squares estimation approaches are applied in which piracy is instrumented with IPRs regimes (treaties), education & ICTs and government quality dynamics. Findings The main finding suggests that, software piracy is good for the poor as it has a positive income-redistributive effect; consistent with economic and cultural considerations from recent literature. ICTs & education (dissemination of knowledge) are instrumental in this positive redistributive effect, while good governance mitigates inequality beyond the piracy channel. Practical implications As a policy implication, in the adoption IPRs, sampled countries should take account of the role less stringent IPRs regimes play on income-redistribution through software piracy. Collateral benefits include among others, the cheap dissemination of knowledge through ICTs which African countries badly need in their quest to become 'knowledge economies'. A caveat however is that, too much piracy may decrease incentives to innovate. Hence, the need to adopt tighter IPRs regimes in tandem with increasing income-equality. Originality/value It is the first empirical assessment of the incidence of piracy on inequality in Africa: a continent with stubbornly high poverty and inequality rates.
Keywords: F42; K42; O34; O15; O55; 330; Inequality; Piracy; Intellectual property rights; Africa